2020
DOI: 10.1080/17513758.2020.1742392
|View full text |Cite
|
Sign up to set email alerts
|

The competition model with Holling type II competitive response to interfering time

Abstract: In Nature, species coexistence is much more frequent than what the classical competition model predicts, so that scientists look for mechanisms that explain such a coexistence. We revisit the classical competition model assuming that individuals invest time in competing individuals of the other species. This assumption extends the classical competition model (that becomes a particular case of the model presented) under the form of a Holling type II term, that we call competitive response to interfering time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Finally, for convenience we set the carrying capacity to K i = 1. Along with the linear case, we will also consider Holling type II and type III functional responses [37][38][39] that incorporate two main forms of saturation functions (see the electronic supplementary material).…”
Section: Methods (A) Multispecies Competition Modelmentioning
confidence: 99%
“…Finally, for convenience we set the carrying capacity to K i = 1. Along with the linear case, we will also consider Holling type II and type III functional responses [37][38][39] that incorporate two main forms of saturation functions (see the electronic supplementary material).…”
Section: Methods (A) Multispecies Competition Modelmentioning
confidence: 99%
“…predator-prey dynamics (Certain et al 2018). For example, functional responses can take different shapes depending on how a species searches, handles and processes prey, with potentially large effects on population dynamics (Spalinger & Hobbs 1992;Koen-Alonso 2007;Castillo-Alvino & Marvá 2020). Additionally, functional responses can vary between habitats and life stages, where a prey species might itself be an important competitor or even predator on young individuals of the predator species (Essington 2004), highlighting the importance of considering population structure.…”
Section: Functional Responsesmentioning
confidence: 99%
“…Recently, Castillo-Alvino and Marvá [15] revisited the classical two species Lotka-Volterra competition model considering the time spent in competition for the interacting species. They proposed the model by incorporating Holling type II competition response to interference time as follows:…”
Section: Model Formulationmentioning
confidence: 99%
“…It is assumed that a 1 ̸ = a 2 . In [15], the authors showed that the more time interfering with competition takes, the more likely coexistence and also obtained multi-stability scenarios. In the above study, the role of predator is not considered.…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation